2022
DOI: 10.1128/spectrum.01928-22
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Selection of Low-Frequency, Lipopolysaccharide-Modified, Colistin-Resistant Mutants with a Combination of Antimicrobials in Acinetobacter baumannii

Abstract: Acinetobacter baumannii has developed resistance to various antimicrobial drugs, and its drug-resistant strains cause nosocomial infections. Controlling these infections has become a global clinical challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…The proposed explanation for the lower prevalence of LPS-deficient colistin-resistant mutants in clinical settings could be the significant negative impact of LPS loss on fitness and virulence, as well as the susceptibility of these isolates to various antibiotics and disinfectants. This was supported by the findings that the lpx mutants grew more slowly compared to the parental wild-type strains in vitro [ 64 , 66 , 68 , 81 , 83 ], while in vitro and in vivo competition tests showed significant fitness costs of colistin resistance [ 81 ]. Determination of the pathogenicity of the lpx mutants also revealed lower cytotoxicity (A549 human alveolar epithelial cells) and attenuated virulence of these strains in the animal models ( Caenorhabditis elegans, Galleria mellonella, and mouse) compared to wild-type or even pmrB mutants [ 63 , 66 , 81 ].…”
Section: Molecular Mechanisms Of Colistin Resistance In a B...mentioning
confidence: 85%
See 4 more Smart Citations
“…The proposed explanation for the lower prevalence of LPS-deficient colistin-resistant mutants in clinical settings could be the significant negative impact of LPS loss on fitness and virulence, as well as the susceptibility of these isolates to various antibiotics and disinfectants. This was supported by the findings that the lpx mutants grew more slowly compared to the parental wild-type strains in vitro [ 64 , 66 , 68 , 81 , 83 ], while in vitro and in vivo competition tests showed significant fitness costs of colistin resistance [ 81 ]. Determination of the pathogenicity of the lpx mutants also revealed lower cytotoxicity (A549 human alveolar epithelial cells) and attenuated virulence of these strains in the animal models ( Caenorhabditis elegans, Galleria mellonella, and mouse) compared to wild-type or even pmrB mutants [ 63 , 66 , 81 ].…”
Section: Molecular Mechanisms Of Colistin Resistance In a B...mentioning
confidence: 85%
“…Accordingly, pmrB mutations could lead to the constitutive activation of PmrA, resulting in increased expression of the pmrCAB and resistance to colistin [ 59 ]. In addition, previous studies reported frequent amino acid substitutions of PmrB at position 170 (P to Y, L, Q, or S) ( Table 1 ) and 315 (G to D, S, or V) in colistin-resistant isolates [ 68 , 70 , 76 , 84 , 86 ]. Although Oikonomou and coauthors [ 69 ] described the PmrB mutations (A138T, A226V, and A444V) repeated in colistin-resistant A. baumannii [ 70 , 72 , 73 , 74 , 76 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ] as not responsible for colistin resistance, the involvement of A138T and A226V in this phenomenon should not be excluded.…”
Section: Molecular Mechanisms Of Colistin Resistance In a B...mentioning
confidence: 92%
See 3 more Smart Citations